Molecular epidemiology of human hepatitis A virus defined by an antigen-capture polymerase chain reaction method. - Jansen, R W (1990)
We describe an immunoaffinity-linked nucleic acid amplification system (antigen-capture/polymerase chain reaction, or AC/PCR) for detection of viruses in clinical specimens and its application to the study of the molecular epidemiology of a picornavirus, hepatitis A virus (HAV). Immunoaffinity capture of virus, synthesis of viral cDNA, and amplification of cDNA by a polymerase chain reaction (PCR) were carried out sequentially in a single reaction vessel. This approach simplified sample preparation and enhanced the specificity of conventional PCR. AC/PCR detected less than one cell culture infectious unit of virus in 80 microliters of sample. Sequencing of AC/PCR reaction products from 34 virus strains demonstrated remarkable conservation at the nucleotide level among most strains but revealed hitherto unsuspected genetic diversity among human isolates. Epidemiologically related strains were identical or closely related in sequence. Virus strains recovered from epidemics of hepatitis A in the United States and Germany were identical in sequence, providing evidence for a previously unrecognized epidemiologic link between these outbreaks.